2010
DOI: 10.1002/jbm.a.32983
|View full text |Cite
|
Sign up to set email alerts
|

Effect of poly(ethylene glycol) diacrylate concentration on network properties and in vivo response of poly(β‐amino ester) networks

Abstract: Poly(β-amino ester) networks have shown promise as tissue scaffolds. The objective of this work was to examine the effect of changing poly(ethylene glycol) diacrylate concentration on poly(β-amino ester) network properties and to assess the degradable polymers' in vivo response, using magnetic resonance imaging (MRI) and immunohistochemistry. The networks were synthesized from hexanediol diacrylate (HDDA), poly(ethylene glycol) diacrylate (PEGDA), and a primary amine, 3-methoxypropylamine (3-MOPA), with a fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
(32 reference statements)
2
16
0
Order By: Relevance
“…Moreover, Safranski et al . showed that degradation rate of PEG-based hydrogels did not affect the thickness of the fibrous capsule or staining intensity for iNOS or Arg1 after 8 weeks of subcutaneous implantation in mice [28], in agreement with our results. Although these studies are not exhaustive, separate groups have now reported the counterintuitive finding that degradation rate does not have a significant effect on macrophage phenotype or on the FBR to crosslinked hydrogels made from both synthetic and natural polymers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, Safranski et al . showed that degradation rate of PEG-based hydrogels did not affect the thickness of the fibrous capsule or staining intensity for iNOS or Arg1 after 8 weeks of subcutaneous implantation in mice [28], in agreement with our results. Although these studies are not exhaustive, separate groups have now reported the counterintuitive finding that degradation rate does not have a significant effect on macrophage phenotype or on the FBR to crosslinked hydrogels made from both synthetic and natural polymers.…”
Section: Discussionsupporting
confidence: 92%
“…One study showed that a decrease in poly(ethylene glycol) (PEG)-based hydrogel stiffness (and increase in swelling ratio) resulted in a decrease in the thickness of the fibrous capsule following implantation in C57BL/6 mice for 28 days, concomitant with a decrease in inflammatory (i.e., M1) gene expression by macrophages [27]. In contrast, another study found that different degradation profiles, and therefore different elastic modulus profiles, of PEG-based hydrogels did not affect macrophage phenotype or the FBR in a similar mouse model [28]. …”
Section: Introductionmentioning
confidence: 99%
“…This diacrylate mixture was combined with 3MOPA at a molar ratio at 1.15:1 to ensure acrylate endgroups. The step-growth polymerization to form degradable PBAE macromers occurred for 24 hours at 200 rpm at 90°C on a JKEM reaction block (RBC-20 with BTS-1500 shaker) following [31,33]. The resulting macromers were verified by 1 H NMR on a Varian Mercury Vx 400 in deuterated chloroform and chemical structure can be found in [33], where the PEGDA units are incorporated between HDDA units of the macromer.…”
Section: Methodsmentioning
confidence: 99%
“…The influence of environment was also examined, where samples were tested in vitro and in vivo to verify that this effect was not limited to an in vitro setting. Three biodegradable crosslinkers, poly(β-amino ester)s with acrylate endgroups, were synthesized with varying levels of hydrophilicity to alter mass loss rate [31, 33]. By combining them with a nondegradable, high Tg monomer, such as methyl methacrylate, the Tg of the network was increased to ambient conditions [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation